سورہ نور میں وارد معاشرتی اصول : ایک جائزہ: Social Principles Mentioned in Surah An-Nur: A Review - Hussain, Mazhar; Zubaida; Ghuni, Dr. Muhammad Ismail (Al-Irfan, 2024)
For our social rules, the rules that Allah has revealed through the Qur'an are in accordance with the nature of man, so we have to apply the rules given by Allah and His Messenger ﷺ in the society, because all the rules and regulations of the world If applied, its effects may remain for some time, but the principles of Islam are always permanent and the people living in the society are satisfied and enjoy these principles. The main reason is that the principles of Islam are equal for all. There is no difference between the rich and the poor. Likewise, the basic principles that Allah has described in Surah Al-Noor, if applied in the society, will become the cradle of peace in the society.